The Impact of Financial Technology on Consumer Behavior and Banking Service - Yatimin, Yatimin; Harahap, Subur; Redjeki, Finny; Suprayitno, Degdo; Sinaga, Hommy Dorthy Ellyany; Nainggolan, Elisabeth; Batjo, Sitti Nurjana (UNIVERSITAS PAKUAN, 2025)
This study aims to evaluate the impact of financial technology (fintech) on consumer behavior and banking services through a meta-analysis approach. Along with the rapid development of digital technology, fintech has changed the way consumers access, use, and respond to financial services. This study analyzes and synthesizes the results of a number of relevant empirical studies to identify the patterns, trends, and strength of fintech's influence on consumer behavior and adaptation of banking services. The results of the meta-analysis show that fintech significantly influences consumer preferences and loyalty, especially in terms of ease of access, time efficiency, and convenience of use ( r = 0.765 ; t = 8.427) medium effect size category. On the other hand, the banking sector showed a diverse response, ranging from strategic collaboration to internal digital transformation. These findings provide important implications for policymakers, financial industry players, and banking institutions in designing adaptive strategies in the digital era.